Education and human capital effect on Malaysian economic growth - Islam, Rabiul; Abdul Ghani, Ahmad Bashawir; Kusuma, Bobby; Theseira, Belinda Barbara (EconJournals, 2016)
In this globalization era, more knowledgeable human capital is needed to gain better economic growth. The ability of a country’s human resources in providing skillful labors in various scopes ensures the success of implementation of the economic policies. Education and human capital has two essential keys that have relation in contributing towards the economic growth. Human capital is a set of resources that combines knowledge, training and skills that is correlated to education. The attention in higher education increases from time to time as people realizing the importance of providing better education for the future of their children and the economy as a whole